(untitled) - Stallings, William (Upper Saddle River, NJ., 2005)
A textbook for an introductory course in information communications intended for business and information management students. The fourth edition adds two chapters in a new part that covers the TCP/IP set of protocols, the Internet, and quality of service.
Keywords: Business,Data transmission systems,Business enterprises; Communication systems,Computer networks; Data processing